AI Sentiment, Innovation Capability, and Strategic Alignment: Impacts on Islamic Bank Performance - Qahtanie, Rafat; Baitsyam, Al Aysan (Inovasi Analisis Data, 2025)
Objective; The purpose of this paper is to examine the influence of AI sentiment, innovation capability, and strategic digital alignment on financial performance of Islamic banks and its moderation by regulatory agility.Methods; Quantitative research through secondary reports, FinBERT sentiment, index-based measures, moderation regression.Results; Results indicate that AI sentiment, innovation capability and strategic digital alignment have significant positive effects on both ROA and ROE, validating their position as antecedents of financial performance. Among these, regulatory agility has a positive direct effect on profitability and strongly moderates such relationships, and particularly increasing the impacts of AI sentiment and digital alignment on asset-based returns. Simple slope analysis also shows that advantages increase stronger for banks in a nimble regulatory environment, whereas equity-based outcomes are less convex in nature regarding regulation.Novelty; This study adds to the literature by combining institutional adaptability with digital and innovation drivers, emphasizing regulatory agility as a performance enhancer of Islamic banking. Connecting micro-level strategies with macro-level regulatory adaptation, the study offers a holistic view that is still missing in finance and management.Research Implication; The results imply that policy makers and practitioners need to develop nimble regulatory frameworks to support innovation and digital transformation initiatives, which in turn sustain financial outcomes while also strengthening ethical compliance and stakeholder trust.